Reasons for the Failure of New Technology-Based Firms: A Longitudinal Empirical Study for Germany - Andreas Pinkwart; Dorian Proksch; Michael Schefczyk; Torsten Fiegler; Cornelia Ernst (Credit and Capital Markets – Kredit und Kapital, 2015)
We analyzed the determinants for the business failure of German New Technology-Based Firms (NTBF) in different financial stages. This included a literature review and creation of a set of propositions for the determinants within the individual stages. On the basis of an empirical and longitudinal dataset including data of 82 NTBFs, we tested a subset of our assumptions. With this, we could prove that the technology, the market, the financing and the management competencies comprise important factors as identified in previous studies. Further, we proved that the factors differ in each investment stage as shown by the significance and the connotation of the correlations. The area of technology was not significant in the first investment stage but in the second. While the determinants proved to be the same in the market area, the connotations of the variables differ in the financial and human resource variables. We showed that the different financial states should be analyzed separately when determining factors of business failure. – – Insolvenzursachen in jungen High-Tech Unternehmen in Deutschland: Eine empirische longitudinale Studie In dem vorliegenden Artikel werden die Insolvenzursachen in jungen High-Tech Unternehmen in Deutschland in verschiedenen Finanzierungsphasen untersucht. Auf Basis einer umfassenden Literaturanalyse werden mögliche Insolvenzursachen für die einzelnen Finanzierungsphasen entwickelt. Mit Hilfe eines longitudinalen Datensatzes von 82 junge High-Tech Unternehmen wurde eine Untermenge dieser Insolvenzursachen empirisch getestet. Dabei konnten frühere Studien in Bezug auf die Technologie, den Markt, die Finanzierung und das Humankapital als wichtige Ursachenbereiche für das Scheitern von High-Tech Unternehmen bestätigt werden. Weiterhin lässt sich anhand der unterschiedlichen Signifikanzen und Vorzeichen der Korrelationen zeigen, dass sich die Insolvenzursachen in den jeweiligen Finanzierungsphasen unterscheiden. Die Variablen im Bereich Technologie sind in der frühen, ersten Finanzierungsphase nicht relevant, wohl aber in der zweiten. Während die marktbezogenen Variablen in allen Finanzierungphasen übereinstimmen, ändern sich die Vorzeichen in den Bereichen Finanzierung und Humankapital. Die longitudinale Analyse legt offen, dass sich die Insolvenzursachen in den einzelnen Finanzierungsphasen signifikant unterscheiden.
Keywords: L260; M130; G240; G330; 330; Business Failure; New Technology-Based Firms; Venture Capital; Longitudinal Study